2019
DOI: 10.1177/2054358119827525
|View full text |Cite
|
Sign up to set email alerts
|

A Validation Study of Administrative Health Care Data to Detect Acute Kidney Injury in the Pediatric Intensive Care Unit

Abstract: Background:Large studies evaluating pediatric acute kidney injury (AKI) epidemiology and outcomes are lacking, partially due to underuse of large administrative health care data.Objective:To assess the diagnostic accuracy of administrative health care data-defined AKI in children admitted to the pediatric intensive care unit (PICU).Design:Retrospective cohort study utilizing chart and administrative data.Setting:Children admitted to the PICU at 2 centers in Montreal, QC.Patients:Patients between 0 and 18 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…Using administrative data is a cost-effective method for examining long-term outcomes in a large population. A systematic review in adults has demonstrated that AKI is identified by administrative health data with low sensitivity, but high specificity; similar results were also obtained from a validation study for identifying AKI in the PICU (42,43). Adult studies have used databases to evaluate the association between AKI and long-term CKD development (22).…”
Section: Discussionmentioning
confidence: 80%
“…Using administrative data is a cost-effective method for examining long-term outcomes in a large population. A systematic review in adults has demonstrated that AKI is identified by administrative health data with low sensitivity, but high specificity; similar results were also obtained from a validation study for identifying AKI in the PICU (42,43). Adult studies have used databases to evaluate the association between AKI and long-term CKD development (22).…”
Section: Discussionmentioning
confidence: 80%
“…Further, administrative database codes are better at detecting stage 3 AKI than stage 1-2 AKI, which would create selection bias. 7 We acknowledge Wei's 2 comment on the greater number of deaths versus kidney failure events contributing to our composite end point. However, the incidence of both kidney failure and death were also separately higher in the dialysistreated AKI cohort.…”
Section: Authors' Replymentioning
confidence: 99%
“…We did not use a combination of AKI and dialysis codes to define dialysis-treated AKI, given that administrative codes for AKI have a low sensitivity (,15%) in children. 7 This would significantly reduce the size of our dialysistreated AKI cohort. Although understanding differences in long-term kidney outcomes after dialysis-treated versus less severe forms of AKI is important, this was not our focus.…”
Section: Authors' Replymentioning
confidence: 99%
“…(1) acute kidney injury, aki, acute renal failure, or continuous renal replacement therapy, and (2) admin * adj3 data * to identify validation studies published since this systematic review, which identified an additional eight studies. A summary of the results of these studies (48)(49)(50)(51)(52)(53)(54)(55) and a selection of those published in the systematic review (56)(57)(58)(59)(60)(61) are included in Table 2. To our knowledge, this represents the most up-to-date summary of validation studies for AKI administrative health research.…”
Section: Validation Studies For Administrative Health Care Data In Akimentioning
confidence: 99%